Users‘ intention to use I-POS web system / Muhammad Aiman Anuar ...[et al.] - Anuar, Muhammad Aiman; Hanapi, Nur Izzati; Anuar, Mohamad Imran; Mohamad Rosma, Mohamad Rahimi; Razlan, Noor Masliana (2020)
I POS (Integrated Point of Sale) Web System is a system developed to manage inventory records aimed at SME (Small Medium Enterprise) business organizations including purchase and sale records, and stock movements using calculation automation systems. There are problems faced by SME business organizations such as lack of tools for inventory management and a lack of skills in monitoring profit and sales records. In addition, improvements need to be made to improve existing systems to better meet current situations and problems that cannot be solved by using present poor systems that make it difficult for SME business organizations to achieve their goals. I POS Web System functions to alert and notify sellers to order stocks of bestselling, exhausted, reduced to ensure stocks are always up-to-date based on the FIFO concept (stocks that have expired will undergo appraisal process whether dumped, recycled, etc.). Besides, I POS Web System will record the number of existing stock, and the seller will be able to identify the amount of stock to be added. Additionally, the I POS Web System can also produce statistics and graphs on high demand items so that sellers are always ready to add stock before they run out. After that, commercialization potential of this system targeted among Malaysia SME business organizations that can use through web based system successfully and also potential of systems to be integrated into mobile applications to be more responsive and flexible to rise up market value of system